Osteopatia hipertrófica secundária a osteossarcoma condroblástico extraesquelético em um cão - Hoffmann, Natalia Martins; da Luz, Mayron Tobias; Vieira, Luisa Lemos; Silveira, Matheus Folgearini; Corrêa, Pâmela da Silva; de Oliveira, Débora Maria Marques Callado (Acta Scientiae Veterinariae, 2017)
Background: hypertrophic osteopathy is a periosteum disturb characterized by diffuse new bone formation which leads to significant thickening and deformity of members. Secondary in nature, it usually follows large pulmonary lesions such as abscesses and neoplasms. Extraskeletal osteosarcomas are rare and extremely malignant mesenchymal neoplasms. They comprise approximately 1% of all domestic animals’ osteosarcomas and develop in the absence of a primary bone lesion. The aim of this paper was to describe a case of hypertrophic osteopathy, involving joints and upper limbs bones including ilium, secondary to a mediastinal chondroblastic osteosarcoma with pulmonary metastasis. Case: A 10-year-old spayed female mixed breed dog, weighing 9 kg, was presented with painful limbs, lameness, hind limbs swelling and a four-month history of weight loss. Radiographic examination revealed bilateral and asymmetric periosteal reactions on diaphyseal and/or epiphyseal areas of all proximal phalanges; metacarpal, metatarsal, carpal and tarsal bones; radius; ulna; tibia; fibula; humerus; femur and right ilium. An increased soft tissue radiopacity was noted on the lateral side of the right knee joint. Thoracic radiographies and ultrasonography suggested the presence of a 5-cm neoplasm or abscess in the left caudal lung lobe. At necropsy, the lobe showed a firm and solid, oval white mass measuring 5.2 x 2.9 cm. Another mass was found in the caudal mediastinum, near the diaphragm, with same color and more irregular aspect, measuring 3.3 cm of diameter. Intense periosteal new-bone formation was seen in the entire length of the four limbs bones, characterized by thickening of the bone surface and formation of irregular trabeculae perpendicular to the cortex. Significant swelling and thickening of the joint capsule was noted in the right knee. There was no microbial growth on aerobic or anaerobic cultures from the masses samples sent to culture. Histopathological examination showed areas of chondroid differentiation, osteoid tissue formation and cell morphology suggestive of chondroblastic osteosarcoma in mediastinal region, with invasion and involvement of the diaphragm and lungs. The analyzed bone fragment had large foci of tissue compaction, peritrabecular bleeding and mineralization of osteoid tissue, permeated by plasma cells and typical lymphocytes. Discussion: Although hypertrophic osteopathy is often characterized as a disease which affects the diaphysis of distal long bones, this case presented a proximal progression of the disease. There was an unusual involvement of joints and ilium, which reinforces the importance of radiographic evaluation of these regions. Further studies on the pathogenesis of the syndrome are required, as its exact mechanisms remain obscure. It is suggested that the term hypertrophic osteoarthropathy should not be consider a misnomer since joint involvement is not exclusive of human form of the disease. Mediastinal masses are important cause of hypertrophic osteopathy. However, this is the first paper the authors are aware of that reports the occurrence of hypertrophic osteopathy secondary to mediastinal osteosarcoma. Finally, although rare, extra skeletal osteosarcoma should be considered in the differential diagnosis of intrathoracic masses in dogs with hypertrophic osteopathy. Timely diagnosis of hypertrophic osteopathy, whose signs of lameness and painful limbs draw the owner’s attention, may favor the diagnosis of severe concomitant diseases.